Pemanfaatan Pinterest Sebagai Sumber Inspirasi Desain Busana - Belia Aurora Karenina Pinem; Keren Apriana Br Sihaloho; Yolanda Gratya Hutauruk; Dina Ampera; Untung Desy Purnamasari (SEMESTA: Jurnal Ilmu Pendidikan dan Pengajaran, 2026)
The development of digital technology has influenced the fashion industry, especially in the process of finding inspiration and developing fashion designs. One of the digital platforms widely used by fashion students and designers is Pinterest. This article aims to explain the role of Pinterest as a source of inspiration in fashion design, identify features that support the creative process, and analyze its influence, advantages, and ethical use in the fashion industry. The research method used is a literature review with a content analysis approach through the study of various books, journals, and relevant scientific articles. The results show that Pinterest helps users find visual references, create moodboards, follow fashion trends, and develop design creativity through features such as pins, boards, save inspiration, and visual search. However, the use of Pinterest also has risks such as plagiarism and design fixation when users rely too heavily on existing references without developing original ideas. Therefore, the use of Pinterest should be accompanied by an understanding of digital inspiration ethics to maintain creativity and originality in fashion design